Strategi Dakwah Nabi Ibrahim Alaihi Al-Salam Dalam Perspektif Pendidikan Islam - Nurul Lailiyah; Qurrotul Ainiyah (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, Prophet Ibrahim was sent by Allah to preach / invite the main people of theBabylonians who were then led by King Namrud to worship only the One God(Tauhid), namely Allah SWT. The main purpose of the preaching of the ProphetIbrahim will be achieved well if supported by the application of a true da'wahstrategy. The main purpose of the mission of Prophet Ibrahim was in line with thegoals of Islamic Education, namely to form Kamil beings (perfect faith, worship andmorality). Therefore, this library research focuses on descriptive analysis of the viewsof Islamic education on the strategy of the preaching of Prophet Ibrahim, using ahistorical and descriptive approach, resulting in conclusions that the strategy of thepreaching of Prophet Ibrahim is in line with the elements of Islamic Education,because it is actually propaganda is an effort to invite a true and perfect monotheisticsociety as the goal of Islamic education itself. Keywords: Strategy of Da'wah, Prophet Ibrahim, Islamic Education